Relationship between ankle strength and range of motion and postural stability during single-leg quiet stance in trained athletes - Trajkovic, N.; Kozinc, Z.; Smajla, D.; Sarabon, N. (Scientific Reports, 2021)
The aim of this study was to determine the relationship between strength of ankle plantar and dorsal flexors and range of motion (RoM), and body sway variables during single-leg quiet stance, in highly trained athletes. The participants for this study were young athletes from 9 disciplines (n = 655). Center of pressure (CoP) velocity, amplitude, and frequency were measured during single-leg quiet stance. Moreover, athletes were measured for passive ankle plantar flexion (PF) and dorsal flexion (DF) RoM, and for rate of torque development (RTD) in the 0-50 (RTD50) and 0-200 ms time windows (RTD200). Ankle strength and RoM could not predict CoP velocity total, anterior-posterior (AP), and medial-lateral (ML) (p > 0.05). However, PFRTD50 and PFRoM and PFRoM positively influenced CoP amplitude in ML direction (p < 0.001, R2 = 0.10). Moreover, CoP frequency in ML direction significantly increased with lower PFRTD50, DFRTD50, DFRTD200, PFRoM, and DFRoM (p < 0.05). We have demonstrated that ankle strength and RoM were related to single-leg quiet stance postural balance in trained athletes. The ankle RoM showed the greatest influence on CoP variables in ML directions.